2016
DOI: 10.1007/s12105-016-0747-0
|View full text |Cite
|
Sign up to set email alerts
|

Well-Differentiated Laryngeal/Hypopharyngeal Liposarcoma in the MDM2 Era Report of Three Cases and Literature Review

Abstract: Laryngeal/hypopharyngeal liposarcomas are very rare, fewer than 40 cases have been reported. These tumors are polypoid, with a male predisposition, and usually cause hoarseness and difficulty breathing. Their clinical course is characterized by multiple local recurrences. No distant metastasis has been reported, and dedifferentiation is extremely rare. In sum, the prognosis of these tumors is excellent; the 5-year survival rate is essentially 100 %. Pathologic diagnosis of these well-differentiated liposarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
2
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 8 publications
0
24
2
4
Order By: Relevance
“…In contrast, Lyle et al [ 45 ] found no MDM2 amplification in their series of ten tests among 38 patients with malignant phyllodes tumor of the breast. Zhu et al [ 46 ] reported the first documented cases of MDM2 amplification in laryngeal and hypopharyngeal liposarcoma. In a separate study by Kato et al [ 47 ], MDM2 has been recognized as a marker of pseudo-progression in patients treated with single-agent checkpoint (PD-1/PDL-1) inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Lyle et al [ 45 ] found no MDM2 amplification in their series of ten tests among 38 patients with malignant phyllodes tumor of the breast. Zhu et al [ 46 ] reported the first documented cases of MDM2 amplification in laryngeal and hypopharyngeal liposarcoma. In a separate study by Kato et al [ 47 ], MDM2 has been recognized as a marker of pseudo-progression in patients treated with single-agent checkpoint (PD-1/PDL-1) inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Deve ser realizada quando não é possível preservar a função do órgão. Já o uso de tratamento adjuvante não é consenso na literatura 4,5 .…”
Section: Discussionunclassified
“…O lipossarcoma é o sarcoma mais comum da vida adulta, representando 20% dos diagnósticos de sarcoma, acometendo principalmente membros inferiores e retroperitônio 3,4 . Desses, apenas 5% são encontrados na região de cabeça e pescoço e apenas uma pequena parcela é encontrada na laringe 5,6 .…”
unclassified
See 1 more Smart Citation
“…[5]  Im Larynx und Hypopharynx gibt es in der Weltliteratur bisher weniger als 40 dokumentierte Fälle. [1,3,4] Ein…”
Section: Diskussionunclassified